The Longitudinal Association between Resting Heart Rate and Psychopathic Traits from a Normative Personality Perspective - Kavish, Nicholas (American journal of criminal justice, 2020)
A large body of research has accumulated investigating the possibility of an association between resting heart rate and psychopathic traits, with meta-analysis suggesting a modest, negative association. Some recent research suggests that prior findings of an association between heart rate and psychopathy may be influenced by inclusion of antisocial behavior in the assessment of psychopathic traits. The current study explores this possibility in a longitudinal sample of British males by comparing resting heart rate at age 18 to psychopathy assessed from a Five Factor Model perspective and from the Psychopathy Checklist: Screening Version (PCL:SV) at age 48. Our psychopathic personality scale, created using the Big Five Inventory (BFI), was significantly correlated with the PCL:SV and was most related to the antisocial factor. In correlation analyses, resting heart rate at age 18 was not significantly related to BFI psychopathy, but was positively related to BFI Openness and Conscientiousness, and these associations held up after controlling for childhood SES, BMI at 18, and whether the participant smoked during the age 18 assessment. Additional analyses controlling for smoking status were conducted to address the biasing effect of smoking on heart rate during the age 18 assessment and a significant, albeit weak, negative association between resting heart rate and BFI psychopathy emerged. Future research should replicate these results using other normative personality approaches to assess psychopathic traits.